Identification of time of death of cats according to histological changes in some organs - Serdioucov, J.; Shkundia, D.; Kruchynenko, O. (Regulatory Mechanisms in Biosystems, 2023)
Determining the time of an animal’s death is an extremely relevant subject in the practice of modern forensic medicine, because the issue often arises when investigating crimes related to animal abuse, in particular, with domestic cats Felis silvestris catus (Linnaeus, 1758). Methods of identifying time of cats’ death are currently developed insufficiently and their introduction into the veterinary-forensic practice has been limited, including the histological method we have employed. We used five corpses of cats, from which we periodically, after certain time periods, gathered the material for histological study, sampling such organs as the liver, kidneys, lungs, heart (myocardium), and the skeletal muscles. From the collected material, we made histological sections and stained them with hematoxylin and eosin. We determined the general patterns in changes occurring in the internal organs of cats over time, namely changes in the staining intensity of the cell elements and intercellular structures on the histopreparations; formation of detritus-filled cavities; a number of distinctive changes in the connective-tissue stroma of the organs; emergence of baciliform bacteria in the tissues and formation of their colonies. In the muscle tissue, we found specific features such as loss of alignment and emergence of transversal grooves with subsequent fragmentation. The study revealed that the development of those changes in each organ clearly correlated with time that has passed since each animals had died. Thus, a complex evaluation of detected changes can give a more accurate – compared with other existing methods – assessment of the time of death of a corpse submitted to forensic veterinary examination. We recommend using the histological method for animals presumed to have been dead for no more than 18 days, because later the tissue disintegration reaches such a level that complicates the correlation of changes with time. We consider it promising to study the time of death of domestic cats using other methods for identifying criteria for postmortem intervals longer than 18 days, and also identifying time of death in other species of animals.